Caracterização genotípica e fenotípica de populações de Jatropha curcas - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
Jatropha curcas is a high economic potential of plant used in different geographic regions of Brazil, however, the genotypes used in plantations are genetically unknown. This study aimed to identify phenotypic plasticity in populations of J. curcas. The experiment was conducted in the experimental field of the State University of Goiás (UEG) - Campus Ipameri, following the completely randomized design with 11 treatments and four replications. In the agricultural year 2014/2015 were analyzed a range of morphological and physiological variables. Morphophysiological wide variations were observed in the descriptive analysis for the different populations of J. curcas. Positive correlations were observed only between the diameter of the crown and seed yield; and canopy diameter and stomatal density in adaxial epidermis, indicating that the diameter of the canopy can be used as a descriptor in breeding programs of plants. Cluster analysis confirmed the existence of diversity among populations of J. curcas, with the formation of two groups, showing that the genetic basis of J. curcas found in different regions of Brazil is close. The analysis of phenotypic plasticity demonstrated that morphological variables showed higher coefficient of plasticity in relation to physiological and productive variables. Among the morphological and productive variables showed higher phenotypic plasticity values were asexual flowers, hermaphrodite, female, male, number of inflorescences per plant, oil yield and seed. The diameter of the crown is the character that directly influences the productivity of J. curcas. The morphological and physiological variables can be used in J. curcas breeding programs to study the diversity and phenotypic plasticity.
Keywords: Biocombustível; Diversidade genética; Oleaginosa; Pinhão manso; Biofuel; Genetic diversity; Oilseeds; Jatropha curcas; CIENCIAS AGRARIAS